2019
DOI: 10.21203/rs.2.16038/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comprehensive analysis on phenotype and genetic basis of Chinese Fanconi anemia patients: dismal outcomes call for nationwide studies

Abstract: Background Fanconi anemia (FA) is the most common inherited bone marrow failure (BMF) syndrome with 22 related genes identified. The ALDH2 rs671variant has been proved related to accelerated progression of BMF in FA patients. The phenotype and genetic basis of Chinese FA patients have not been investigated yet.Methods We analyzed the 22 FA-related genes of 63 BMF patients suspected to be FA. Clinical manifestations, morphological and cytogenetic feathers, ALDH2 genotypes, treatment, and outcomes of the definit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Our sensors provide a toolkit that may help to improve our understanding of the potential roles of FA in various cellular processes. Some recent research examined Fanconi anemia patients and found that people holding the ALDH2 dominant-negative variant (ALDH2*2) had the tendency of accelerated progression of bone marrow failure (BMF) 48,49 . Study on Fancd2, Aldh2 and Adh5 knockout mice have indicated the effect of increased endogenous formaldehyde in the process 4,5 .…”
Section: Discussionmentioning
confidence: 99%
“…Our sensors provide a toolkit that may help to improve our understanding of the potential roles of FA in various cellular processes. Some recent research examined Fanconi anemia patients and found that people holding the ALDH2 dominant-negative variant (ALDH2*2) had the tendency of accelerated progression of bone marrow failure (BMF) 48,49 . Study on Fancd2, Aldh2 and Adh5 knockout mice have indicated the effect of increased endogenous formaldehyde in the process 4,5 .…”
Section: Discussionmentioning
confidence: 99%